Al-Ghazali’s ma’rifah and mahabbah’s relations - Mansoureh Ebrahimi; Gholami, Ahmadali; Kamaruzaman Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2021)
A salik is a ṣufī who practices tasawuf (mysticism) with certain maʻrifah (knowledge of Allah) consequent to their devotion to his/her beloved (God); which piety obtains greater maḥabbah (love) and a more intimate pool of maʻrifah. This paper aims to discuss the concept of maʻrifah in al-Ghazali’s Kimiya’ al-Sa`adah and Iḥyā᾽ʻUlum al- Dinn as an initial element of creation and direct result of maḥabbah (love). The qualitative approach is employed. Literature from peer-reviewed and refereed journals, articles and those two books were reviewed in order to reveal the significant spirit of love and knowledge’s relations in al-Ghazali’s viewpoint as one of the greatest Muslim philosophers, theologians and jurists. The results show that maʻrifah and mahabbah haqiqi (true love and knowledge) are of the same essence and that only those of proven capacity can understand metaphysical domains. Al-Ghazali’s perpective reveals that understanding maʻrifah and mahabbah activates a causal chain or continuum that advances, strengthens and motivates this relationship.